2013
DOI: 10.1371/journal.pone.0064466
|View full text |Cite
|
Sign up to set email alerts
|

Higher Frequency Network Activity Flow Predicts Lower Frequency Node Activity in Intrinsic Low-Frequency BOLD Fluctuations

Abstract: The brain remains electrically and metabolically active during resting conditions. The low-frequency oscillations (LFO) of the blood oxygen level-dependent (BOLD) signal of functional magnetic resonance imaging (fMRI) coherent across distributed brain regions are known to exhibit features of this activity. However, these intrinsic oscillations may undergo dynamic changes in time scales of seconds to minutes during resting conditions. Here, using wavelet-transform based time-frequency analysis techniques, we in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 53 publications
0
35
0
Order By: Relevance
“…The results are not consistent with the well-known strength of the structural links between the MPFC and PCC (Khalsa et al, 2014). We think that this is due to weakening effective connections of MPFC and PCC at rest, as were previously shown by Li et al (2012) and Razi et al (2015), although there are alternative data (Bajaj et al, 2013). Our conclusion can be supported by the data on the weakening of connections between functional networks in the resting state and their strengthening in the task performance (Di et al, 2013).…”
Section: Discussionmentioning
confidence: 56%
“…The results are not consistent with the well-known strength of the structural links between the MPFC and PCC (Khalsa et al, 2014). We think that this is due to weakening effective connections of MPFC and PCC at rest, as were previously shown by Li et al (2012) and Razi et al (2015), although there are alternative data (Bajaj et al, 2013). Our conclusion can be supported by the data on the weakening of connections between functional networks in the resting state and their strengthening in the task performance (Di et al, 2013).…”
Section: Discussionmentioning
confidence: 56%
“…These networks and their properties have been assessed by using neuroanatomical and neurophysiological studies in animals, 10 as well as different brain imaging techniques and analyses in humans. 3946 In humans, several types of networks have been reported: functional brain networks based on evoked responses 37 or intrinsic connectivity of the brain during rest; 3941,44,45 structural networks based on grey matter parameters 47 and white matter properties; and anatomical networks based on white matter connectivity. 48 Both evoked and resting state studies performed in patients with IBS have demonstrated abnormalities in regions and task-related networks linked to emotional arousal, 4953 central autonomic control, 6,5456 central executive control, 51,57,58 sensorimotor processing 6,5961 and salience detection.…”
Section: The Nervous System Componentmentioning
confidence: 99%
“…Slow-6, Slow-3 and Slow-2 frequency bands were discarded as they mainly reflect low-frequency drifting, white matter signals and high-frequency physiological noise (Biswal et al, 1995;Zuo et al, 2010) and classifiers obtained by support vector machine (SVM) are sensitive to noise (Guyon et al, 1996). Recent study suggested that Slow-3 frequency band is also meaningful (Bajaj et al, 2013). As the TR of UCLA site is 3 s, cannot fully cover the whole Slow-3 frequency band, we also discarded the Slow-3 band.…”
Section: Frequency Band Selectionmentioning
confidence: 99%